Comparisons of Karnofsky Score, Quality of Life, and Glomerular Filtration Rate in Cervical Cancer Patients with Bilateral Obstructive Uropathy before and after DJ Stent Insertion - Daryanto, Besut; Wijaya, Mangkubumi Putra; Seputra, Kurnia Penta (Jurnal Kedokteran Brawijaya, 2026)
Cervical cancer is the second most common cancer in Indonesia, and it can lead to urinary tract obstruction. Obstructive uropathy can progress to hydronephrosis and kidney failure with a poor prognosis and can lead to several complications such as sepsis and uremia.  This study aims to compare outcomes of advanced-stage cervical cancer patients with obstructive uropathy who underwent DJ stent insertion versus those who did not at Saiful Anwar Malang General Hospital in Indonesia. An observational study conducted with a prospective cohort approach. Data collection was done through purposive sampling. Inclusion criteria include cervical cancer patients with bilateral obstructive uropathy who undergo DJ stent insertion and who failed or refused DJ stent insertion at the Saiful Anwar General Hospital. Paired T-tests were conducted to compare patients before and after DJ stent insertion, and unpaired T-tests were performed to compare patients who underwent DJ stent insertion and who did not. Glomerular Filtration Rate (GFR), Karnofsky Score (KS), and Quality of Life (QoL) Values before DJ stent insertion were 0.382, 0.454, and 0.246, respectively. After 3 months, these values were found to be 0.002, 0.000, and 0.002, respectively. DJ stent insertion has been proven to improve the quality of life, performance status, and kidney function in patients with cervical cancer and obstructive uropathy.